2016
DOI: 10.3847/0004-637x/821/1/41
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF LINEARLY POLARIZED 6.9 mm CONTINUUM EMISSION FROM THE CLASS 0 YOUNG STELLAR OBJECT NGC 1333 IRAS4A

Abstract: We report new Karl G. Jansky Very Large Array (JVLA),  0. 5 angular resolution observations of linearly polarized continuum emission at 6.9 mm, toward the class 0 young stellar object NGC 1333 IRAS4A. This target source is a collapsing dense molecular core that was resolved at short wavelengths to have an hourglass shaped B-field configuration. We compare these 6.9 mm observations with previous polarization Submillimeter Array observations at 0.88 mm, which have a comparable angular resolution (∼  0. 7). We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…We report a similar two-lobe structure for the first time in NGC 1333 IRAS4B and detect peaks of polarization intensity on each side of the north-south outflow. Liu et al (2016) have found that the polarization intensity of NGC 1333 IRAS4A observed at 6.9 mm has a more typical distribution in which the polarization intensity peaks toward the source center; these authors have attributed this variation of the polarization distribution with wavelength to optical depth effects. Our temperature brightnesses rather suggest that the 0.87 mm emission is optically thin at the envelope scales probed in this paper, for all our objects.…”
Section: Potential Causes For Depolarizationmentioning
confidence: 99%
“…We report a similar two-lobe structure for the first time in NGC 1333 IRAS4B and detect peaks of polarization intensity on each side of the north-south outflow. Liu et al (2016) have found that the polarization intensity of NGC 1333 IRAS4A observed at 6.9 mm has a more typical distribution in which the polarization intensity peaks toward the source center; these authors have attributed this variation of the polarization distribution with wavelength to optical depth effects. Our temperature brightnesses rather suggest that the 0.87 mm emission is optically thin at the envelope scales probed in this paper, for all our objects.…”
Section: Potential Causes For Depolarizationmentioning
confidence: 99%
“…In addition, highresolution VLA observations revealed that the well-studied low-mass Class 0 protostar NGC 1333 IRAS 4A is significantly polarized at 8 mm, again with the near side brighter than the far side in polarized intensity Liu et al 2016). The source is so bright that it is believed to be optically thick out to 7 mm (Liu et al 2016), which is consistent with the interpretation that the polarization comes from scattering, at least near the center (see also Yang et al 2016b). Although it is conceivable that in each of the sources the asymmetry could be produced by an intrinsic feature on the disk, such a dust trap, it is statistically unlikely for such a trap to occur on the near side for all three cases.…”
Section: Evolution Of Dust Settling From Polarization Of Inclined Disksmentioning
confidence: 99%
“…The initial searches for disk polarization yielded only upper limits (Hughes et al 2009(Hughes et al , 2013. These were soon followed by detections in IRAS 16293B (Rao et al 2014) using the Submillimeter Array (SMA), in HL Tau (Stephens et al 2014), L1527 (Segura- Cox et al 2015), and Cepheus A HW2 (Fernández-López et al 2016) using the Combined Array for Research in Millimeter-wave Astronomy (CARMA), and in NGC 1333 IRAS 4A at 8 mm and 1 cm Liu et al 2016) using the Karl G. Jansky Very Large Array (VLA). Most excitingly, there are a large number of approved disk polarization programs using Atacama Large Millimeter/submillimeter Array (ALMA), with some results already published (Kataoka et al 2016b) and several more in preparation (e.g., J. M. Girart, in prep).…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al 2013;Hull et al 2013;Zhang et al 2014;Cox et al 2015;Ching et al 2016;Liu et al 2016;Planck Collaboration Int. XXXIII 2016, also see H.-B.…”
mentioning
confidence: 99%